Estimation of Equivalent Conicity from Contactless Measurements of Wheel and Rail Profiles. Issue 1 (1st June 2022) - Pugi, L.; Bocciolini, L.; Piccioli, F.; Massini, D.; Cherici, G.; Lo Scalzo, L.
Abstract: Measurement of Equivalent Conicity is quite important index to properly evaluate geometric quality of rails and wheels. The way in which this index is evaluated is evaluated is described by the standard EN 15302 from online contactless measurement of rail profiles performed by a dedicated measurement coach. The numerical treatment of large amount of data derived by the acquisition of a huge number of measured rail profiles should be performed with great accuracy but also with a great numerical efficiency to assure a near to real time evaluation of performed analysis. In this work authors describe an efficient procedure developed using open-source software that has been developed to meet accuracy, efficiency, and portability specifications. Paper investigates how different integration and smoothing should affect efficiency and accuracy of performed operations. Proposed approach is first validated on numerical synthetic inputs and then validated on experimental data, also comparing performances of the proposed software with a commercial one. Results are encouraging, demonstrating the feasibility of the proposed approach for the realization of flexible and efficient tools for Real-Time implementation of the estimation of equivalent conicity for railway applications.